Confinement, Food security and consumption of subsidized products in Tunisia: Worsening trade deficit - Nafti, Sawssen (Technium Social Sciences Journal, 2022)
The present paper attempts to know if the confinement in Tunisia has an impact on the consumption of subsidized products and in turn on food security and on the trade balance or not. Firstly, by analyzing the place of subsidized products in Tunisian economy. Then via the determination of limits of confinement in Tunisia specially trade deficit. Finally through the analysis of different problems given by confinement on food security and increased of percentage of cancer. According to our analysis, confinement of COVID-19 pandemic has caused an unprecedented economic, food security and financial crisis in Tunisia especially on the trade deficit witch is suffer before of various difficulty. The confinement can be considred a good solution for COVID but it have many limits on food security for Tunisian and on incresed of consumption of subsidized products in Tunisia.